Estudo teórico de propriedades eletrônicas de nanoestruturas de carbono - Ritter, Carlos Ferreira (2010)
In this thesis we develop theoretical studies on the electronic properties of some graphitic carbon based systems: graphene nanoribbons, graphene multi-terminal devices and carbon nanotubes. The adopted model calculation is based on the tight-binding approximation, the Green's functions theory, the decimation and renormalization method and the Landauer-BÄuttiker formalism for electron conduction. We have considered as well the Peierls approximation to describe systems submitted to magnetic fields. The studies presented here are divided in three major focusses. The first one consists of an analysis of the electronic properties of graphene nanoribbons and how these properties respond to applied electric and magnetic fields. In this ¯rst part, we focus mainly in the possibility of generating energy gap modulations and present a self-consistent treatment of the electronic distribution. In the following, we describe the transport properties of multi-terminal systems containing vacancies at the central conductor. We explore the possibility of electronic transport tuning by means of single and multiple vacancies, highlighting the importance of the graphene sublattices, the presence of additional semiconductor terminals and the formation of delocalized defect states. The third main focus of the work is the realization of a theoretical model for a carbon nanotube based molecular nano-sensor. In this case, we represent a molecule bonded to the nanotube's wall by a local normal vibrational mode with phonon and electron-phonon coupling characteristic energies. The basic idea for the device's operation is that the characteristic energies can be measured from the e®ects caused by the mode in the electronic transport. This comes from the fact that conduction electrons from the nanotube may be scattered inelastically by the phonons associated to the molecule. Last, we present some preliminary results of new electronic properties modulations generated in graphene nanoribbons and carbon nanotubes, when these are submitted to gate voltages that create energy barrier type interfaces. The goal of this study is to explore several geometries for these interfaces so that we can manipulate the electronic distribution and concentrate it in small regions as a focusing scheme. This could be envisaged as a mechanism for the generation of localized magnetic moments.